2020
DOI: 10.1007/s00405-020-06355-3
|View full text |Cite
|
Sign up to set email alerts
|

OSA in patients with head and neck cancer is associated with cancer size and oncologic outcome

Abstract: Purpose Obstructive sleep apnea (OSA) is associated with severe daytime sleepiness and reduced quality of life. These symptoms are also present in patients with squamous cell carcinoma of the head and neck (SCCHN) before, during and after treatment, so that comorbidity cannot be excluded. The aim was to evaluate the prevalence of OSA and its impact on the quality of life in patients with oropharyngeal, hypopharyngeal and lateral tongue SCCHN in a prospective study. Methods We performed cardiorespiratory home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…Li and colleagues described OSA severity as a risk factor that contributed to short overall survival in patients with lung cancer [6]. A study by Huppertz and colleagues demonstrated a significant association between recurrent disease or cancer-related mortality and higher AHI in patients with head and neck squamous cell carcinoma (HNSCC) [16].…”
Section: Obstructive Sleep Apnea and Cancer Riskmentioning
confidence: 99%
See 4 more Smart Citations
“…Li and colleagues described OSA severity as a risk factor that contributed to short overall survival in patients with lung cancer [6]. A study by Huppertz and colleagues demonstrated a significant association between recurrent disease or cancer-related mortality and higher AHI in patients with head and neck squamous cell carcinoma (HNSCC) [16].…”
Section: Obstructive Sleep Apnea and Cancer Riskmentioning
confidence: 99%
“…Regarding HNSCC, different authors reported coexisting OSA [14][15][16][17][18][19][40][41][42][43][44][45]. Worldwide, over 500,000 new cases of HNSCC are reported annually, being the seventh most common type of cancer [20,46].…”
Section: Obstructive Sleep Apnea Might Be a Relevant Comorbidity Of Head And Neck Cancermentioning
confidence: 99%
See 3 more Smart Citations